Efektivitas Terapi Relaksasi Otot Progresif Terhadap Tekanan Darah Pada Lansia Di Perumahan Pondok Mutiara Asri Malang - Shalu Nafisah Aldini; Mizam Ari Kurniyanti; Abdul Qodir (Yayasan Jompa Research and Development, 2023)
The high rate of people with hypertension is one of the problems that affect the degree of public health . The cause of increased hypertension is due to lifestyle changes such as one of them is lack physical activity. One of the physical activities that can be done to do progressive muscle relaxation therapy. This progressive muscle relaxation therapy is a therapy that is affordable, practical, has no side effects, makes the body relax and the mind calm. The purpose of this researce is etermine the effectiveness of progressive muscle relaxation therapy on blood pressure in the elderly in Pondok Mutiara Asri Regency Malang. This study used quasi-experiment with pretest and posttest control group design. The number of samples used was 30 respondents that was taken by total sampling technique which was divided into 15 respondents in intervention group and 15 people in control group. The measuring instruments used were Spygnomanometer with SOP blood pressure guidance. The data analyse tests used were the Wilcoxon test and the Mann-Whitney test. The results of the analysis obtained the average results of blood pressure in the intervention group before and after the administration of progressive muscle relaxation technique therapy, namely systolic blood pressure was 156.80 mmHg and 125.67 mmHg, while diastolic blood pressure was 71.33 mmHg and 61.33 mmHg and p-value 0.001 and 0.001 (<0.05), so it can be concluded that effectiveness of progressive muscle relaxation therapy on blood pressure in the elderly. The conclusion of this study is there is an effect of progressive muscle relaxation therapy on blood pressure in the elderly in Pondok Mutiara Asri Regency Malang.